Skin asepsis protocols as a preventive measure of surgical site infections in dogs: chlorhexidine–alcohol versus povidone–iodine - Luís Belo; Isa Serrano; Eva Cunha; Carla Carneiro; Luis Tavares; L. Miguel Carreira; Manuela Oliveira (BMC Veterinary Research, 2018)
Abstract Background Most of surgical site infections (SSI) are caused by commensal and pathogenic agents from the patient’s microbiota, which may include antibiotic resistant strains. Pre-surgical asepsis of the skin is one of the preventive measures performed to reduce SSI incidence and also antibiotic resistance dissemination. However, in veterinary medicine there is no agreement on which biocide is the most effective. The aim of this study was to evaluate the effectiveness of two pre-surgical skin asepsis protocols in dogs. A total of 46 animals were randomly assigned for an asepsis protocol with an aqueous solution of 7.5% povidone-iodine or with an alcoholic solution of 2% chlorhexidine. For each dog, two skin swab samples were collected at pre-asepsis and post-asepsis, for bacterial quantification by conventional techniques and isolation of methicillin-resistant species. Results Most samples collected at the post-asepsis did not present bacterial growth, both for the animals subjected to the povidone-iodine (74%) or to the chlorhexidine (70%) protocols. In only 9% of the cases a significant bacterial logarithmic reduction was not observed, indicating possible resistance to these agents. Also, the logarithmic reduction of the bacterial quantification from pre- and post-asepsis time, was not statistically different for povidone-iodine (6.51 ± 1.94 log10) and chlorhexidine (6.46 ± 2.62 log10) protocol. From the 39% pre-asepsis swabs which showed bacterial growth in MRSA modified chromogenic agar medium, only one isolate was identified as Staphylococcus aureus and one as S. epidermidis. False positives were mainly other staphylococci species, as well as Enterobacteriaceae. Conclusions Pre-surgical skin asepsis protocols with povidone-iodine or chlorhexidine showed similar efficacy in the elimination of methicillin resistant bacteria and preventing surgical site infections in dogs undergoing surgery.